Perancangan Sistem Administrasi Barang Berbasis Web Menggunakan Model Pengembangan Sistem RAD - Fattah Al Ikhsan Ramadhan; Besus Maula Sulthon (Resolusi : Rekayasa Teknik Informatika dan Informasi, 2023)
PT Grandspot Cipta Solusi is a company engaged in the field of information technology which focuses on leasing systems and hardware for call centers. The recording of hardware data is still done manually through Excel media files. The current manual recording method is less effective and efficient and has the potential for data discrepancies and loss of goods. Therefore, we need a system that can help work so that it becomes more effective and efficient. The system development model used in designing this system is Rapid Application Development or RAD. Rapid Application Development is a fast system development method that usually takes 60 to 90 days. There are 4 stages in this method, namely: 1) Requirement Planning stage, 2) Design, 3) Construct, 4) Cutover. Entity Relationship Diagram is a depiction of a database conceptual design that represents the relationship between objects in the real world. PostgreSQL is one of the database software that has been actively developed to date and has been tested for its reliability. PHP is a programming language that can be integrated with HTML. The Goods Administration System is a system designed to help the user's work. With the creation of this system, it can make it easier for users to record existing hardware and make it easier for users to make reports addressed to superiors. In addition, recording also becomes more organized so that the user's work becomes more effective and efficient.